"Hyper‐bright" Near‐Infrared Emitting Fluorescent Organic Nanoparticles for Single Particle Tracking. (3rd February 2014) - Genin, Emilie; Gao, Zhenghong; Varela, Juan A.; Daniel, Jonathan; Bsaibess, Talia; Gosse, Isabelle; Groc, Laurent; Cognet, Laurent; Blanchard‐Desce, Mireille
<x xml:space="preserve">Abstract</x> An efficacious strategy to obtain photostable hyper‐bright near‐IR emitting fluorescent organic nanoparticles (HIFONs) is reported. These HIFONs show excellent chemical and colloidal stability and retain their pristine nanostructure and brightness after incubation in cellular environments. They can be identified at the single particle level with a wide‐field microscope, emerging as highly promising tools for applications in bio‐nanotechnologies. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>